Application of Modern Architecture in Lambaro Traditional Central Market - ibnu aulia (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Traditional markets are often considered to be one of the places giving an impression or picture that is not good for a city's aesthetics. This is also the case with the new Lambaro Central Market located in Aceh Besar. Weak market management and structuring, insufficient facilities and infrastructure, growing numbers of traders are causing market overcrowding and lack of comfort and security. The emergence of traffic jams around the Lambaro Central Market is another influence.                   Although the traditional market still has issues, the community's interest in holding shopping on the market still exists, such as in the towns of Banda Aceh and Aceh Besar. The price of inexpensive and affordable goods is one of the key factors that still make consumers prefer conventional markets as their main shopping destination for everyday needs. Many traders in this market from inside and outside Aceh rely on the results of their wares.                   The presence of the Central Traditional Market of Lambaro still has the potential to continue to grow in a better direction to boost the economy of the city and enable the population to meet their daily needs. Redesigning the Lambaro Central Traditional Market in Aceh Besar is one solution to this issue. The redesign is accomplished by enhancing the standard of the market, increasing comfort and safety, introducing certain types of needs, while still retaining the object's characteristic parts. The theme chosen is Modern Architecture, which is expected to solve object problems and change the image of traditional markets for the better, helping to improve the economy of Aceh's city and citizens, particularly Aceh Besar.